PERANAN KOMITE AUDIT DALAM HUBUNGAN PRESSURE DAN FINANCIAL STATEMENT FRAUD - Mardiana, Ana; Jantong, Alfonsus (Program Pascasarjana STIE Amkop Makassar, 2020)
This study used a purposive sampling method in which out of 144 manufacturing companies listed on the Indonesia Stock Exchange a sample was obtained by 35 companies for 5 consecutive years, so the number of observations was 175. The analytical method used was moderating regression analysis. The results of this study indicate that (1) external pressure has a significant negative effect on financial statement fraud, (2) financial targets have a positive and insignificant effect on financial statement fraud, (3) the audit committee is able to moderate the relationship of external pressure to financial statement fraud, and (4 ) The audit committee does not moderate the relationship of financial targets to financial statement fraud. This shows that external pressure and financial targets do not affect the financial statement fraud, however, with the supervision of the audit committee, it will emphasize the opportunity for financial statement fraud caused by external pressure from the principal. Keywords: External Pressure, Financial Target, Financial Statement Fraud, Audit Committee